Kesepakatan Perjanjian Internasional yang Dilanggar dan Akibat Hukumnya - Bagus, Nurlina; Tuhulele, Popy; Leatemia, Wilshen (Faculty of Law Universitas Pattimura, 2025)
International treaties are formed with the aim of becoming the basis for solving problems in the future so that the parties are protected, get legal certainty, and justice. The process of forming international agreements, countries must comply with the rules of international law regarding the making of international agreements. Indonesia has accelerated the ban on exporting nickel ore in 2020. The European Union sued Indonesia at the WTO court because it was deemed to have violated the GATT-WTO agreement. The purpose of this study is to find out and analyse whether international agreements that have been agreed upon by participating countries can be violated and to find out and analyse the legal consequences of the implementation of the international agreements in question. The results of this study indicate that, International Agreements that have been agreed upon by participating countries can be violated because there are certain circumstances that can be violated. by participating countries can be violated because there are certain circumstances that justify the act of violation as stipulated in the 1989 Vienna Convention justifying the act of violation as stipulated in the 1989 Vienna Convention on International Treaty Law, and the 1969 Vienna Convention which provides guidelines and principles in international agreements.